Continuous Glucose Monitoring Introduction in Internal Medicine Residency Clinic in Patients with DM Type 1 and Type 2 - Andre Manov; Elizabeth Benge; Samera Baig; Sukhjinder Chauhan (Research Highlights in Disease and Health Research Vol. 9, 2023)
This chapter introduced Continuous Glucose Monitoring (CGM) in Internal Medicine Residency Continuity clinic. We started following the blood glucose with CGM in 11-patients with type 1 and Type 2 diabetes mellitus (DM 1 and DM 2) uncontrolled on 3-4 injections of Insulin per day. Continuous glucose monitoring is associated with improved health behaviors and outcomes, such as reductions in glycated hemoglobin (HbA1c), hypoglycemia, body weight, and caloric intake, and increases in physical activity, treatment satisfaction, and adherence to a personal eating plan The CGM was initiated by Internal Medicine and Transitional year Residents who formed the CGM team and adjustment of the Insulin dose based on the CGM data was done actively by them under the supervision of Board-Certified Endocrinologist who was a member of the clinic. The goal was to show improvement of patient’s HbA1c measured by glucose management Indicator. The other goal was to decrease the time spend by our patients in level 1 hypoglycemia between 69-54 mg/dl and in level 2 hypoglycemia less than 54 mg/dl to less than 4% and 1 % respectively per day. The other target of our project was achievement of blood glucose between 70-180 mg/dl - time in range (TIR) in 24-hour period of 50-70% of the time and achievement of low glucose variability measured by coefficient of variation(CV) of less than 36% per day. All these goals were based on American Diabetes association (ADA) recommendation goals while using CGM. Our results were excellent. The HbA1c was reduced in 3- months after introduction of the CGM from 10.5% to 7.47%, the time spent by our patients in level 1 hypoglycemia with blood sugar less than 70 mg/dl was 7- minutes per day (less than 4%) from 27- minutes per day. The time spent in level 2 hypoglycemia decreased to 3- min per day (less than 1%) from 7 minutes per day after switching from SMBG to CGM. We achieved Time in range of 62% per day which was within the ADA goal based on patients’ characteristics. The glucose variability was 29% below the goal of 36% which was also excellent. The patient satisfaction with the CGM devise measured by CGM Quality of life questionnaire was very good. The unique feature of this study was that the successful introduction of the CGM was done by Internal Medicine and Transitional year Residents under the supervision of Board-Certified Endocrinologist which we were not aware that it was done before in USA. The CGM device used in our study was Dexcom G6, because of lack of need of calibration compare to some other CGM devices and availability to us.